2020
DOI: 10.1002/ccd.29227
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, predictors, and outcomes of patient prosthesis mismatch in women undergoing TAVI for severe aortic stenosis: Insights from the WIN‐TAVI registry

Abstract: Objective: To evaluate the incidence, predictors and outcomes of female patients with patient-prosthesis mismatch (PPM) following transcatheter aortic valve intervention (TAVI) for severe aortic stenosis (AS). Background: Female AS TAVI recipients have a significantly lower mortality than surgical aortic valve replacement (SAVR) recipients, which could be attributed to the potentially lower PPM rates. TAVI has been associated with lower rates of PPM compared to SAVR. PPM in females post TAVI has not been inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The multicenter WIN-TAVI registry ( 45 ), which exclusively enrolled female patients, reported a PPM rate of 32.8%. As described in other studies, in this cohort of female patients higher BMI and smaller TAVI prostheses were the only independent predictors of PPM.…”
Section: Impact Of Ppm After Tavimentioning
confidence: 99%
“…The multicenter WIN-TAVI registry ( 45 ), which exclusively enrolled female patients, reported a PPM rate of 32.8%. As described in other studies, in this cohort of female patients higher BMI and smaller TAVI prostheses were the only independent predictors of PPM.…”
Section: Impact Of Ppm After Tavimentioning
confidence: 99%
“…The reported PPM rates after SAVR vary more widely than after TAVR, ranging from 8% to almost 80% in SAVR and from 24% to 35% in TAVR. 13,14 We further looked into the incidence of PPM following redo AVR, in which severe PPM after SAVR ranges from 2% to 9% and after valve-in-valve TAVR ranges from 14% to 33%. Short-and midterm survival benefit of the transcatheter approach was not impacted by higher rates of PPM in valve-invalve TAVR.…”
Section: Summary Of the Resultsmentioning
confidence: 99%
“…There are several baseline clinical characteristics, previously discussed for SAVR, which are also predictive of PPM in TAVR. As seen in SAVR, female sex, younger age, higher BMI, and smaller aortic annulus diameter have all been reported as independent risk factors for the development of PPM in TAVR 14 , 38 EOA indexed to body surface area, however, may lead to an overestimation of PPM in patients with obesity. Thus, recent recommendations suggest applying lower cutoff values of EOA in the patient with BMI ≥ 30: 0.70–0.56 cm 2 /m 2 for moderate PPM, and ≤0.55 m 2 /m 2 for severe PPM 40 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this issue of the journal, Panoulas et al 4 reported the results of a subanalysis of the WIN‐TAVI registry focused on the occurrence of PPM in women after TAVR. The paper has the commendable merit of combining the need for more data on PPM post TAVR with the cogent need to have gender‐specific data for TAVR.…”
mentioning
confidence: 99%